The Influence of Economic Law on a Just Energy Transition - Purnomo, Vicki Dwi; Hamid , Arifin; Tedjosaputro, Liliana (PT FORMOSA CENDEKIA GLOBAL, 2024)
A just energy transition is an essential process in achieving environmental, economic, and social sustainability, by shifting energy use from fossil fuels to renewable energy. In Indonesia, economic law plays a significant role in supporting or hindering this transition process. Its influence includes investment regulations in the renewable energy sector, distribution of energy subsidies, taxation, employment policies, and equitable energy access for the community. Economic law that supports a just energy transition must create a conducive environment for renewable energy investment, reduce dependence on fossil fuels through subsidy reform, and ensure social protection for affected workers. In addition, appropriate taxation policies and environmental law enforcement are needed to encourage widespread adoption of clean energy. With an integrated legal approach, Indonesia can accelerate a just and sustainable energy transition, while ensuring social justice and energy access for all levels of society.